VARIABEL PENGETAHUAN DALAM PENELITIAN KESEHATAN MASYARAKAT - Mardhiati, Retno (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Researches in public health area often used composite variable. The composite variable usedin public health researches includes health knowledge, attitude, intention, motivation, behavior, andmany other more. The objective of this study is to provide an overview of data processing andanalysis on composite variables in public health research. This study used a descriptive designmethod. Two scientific work assignments were used as the example of composite variable dataprocessing which were selected using purposive sampling technique. Descriptive analysis was usedto analyze data. The result shows that the composite variable consists of several items of questionor statement. The creation of the knowledge composite variable started by determining the answerkey of the question or statement item. The correct answer was then scored and totaled. Severalstudies continue to create categorical variables for knowledge composite variables. The categoriescan be sorted into 2 groups or more. The total score of knowledge composite variables can begrouped using mean or median value as the cut off point. Mean value can be used if the totalknowledge score variable has a normal distribution, while median value is used if the distributionis not normal. The grouping of knowledge composite variables can also be done based on the valueof Q1 (quartile 1) or Q3 (quartile 3). Finally, previous reference classification can be used to groupthe variable.